The Effect of Artificial Intelligence Integration and Big Data Analytics on Sustainability reporting Audit Quality with ESG Disclosure and Operational Complexity as Moderating Variables - Inez Permatasari; Noer Sasongko (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study investigates the effects of Artificial Intelligence (AI) and Big Data Analytics (BDA) on Sustainability Reporting Audit Quality (SRAQ) with ESG Disclosure (ESGD) and Operational Complexity (OC) as moderating variables. This research addresses the limited empirical evidence regarding the effectiveness of digital audit technologies in sustainability assurance practices, particularly within Indonesian energy sector companies. The research applied a quantitative associative method based on secondary data derived from the annual and sustainability reports of energy companies listed on the IDX for the 2022–2024 period. The purposive sampling technique resulted in 46 companies with 138 observations. The data were analyzed using SPSS version 25 by applying descriptive statistical analysis, classical assumption testing, and Moderated Regression Analysis (MRA). The findings indicate that Big Data Analytics significantly affects Sustainability Reporting Audit Quality, while Artificial Intelligence does not significantly affect Sustainability Reporting Audit Quality. In addition, ESG Disclosure and Operational Complexity are unable to moderate the relationships between AI, BDA, and Sustainability Reporting Audit Quality. These findings suggest that AI implementation in Indonesian energy companies remains relatively limited due to technological readiness and sustainability assurance challenges, whereas BDA has been more effectively utilized in sustainability auditing practices. Theoretically, this study extends to the sustainability auditing literature through the integration of digital audit technologies, ESG disclosure, and operational complexity within a single research framework based on Stakeholder Theory and Contingency Theory. Practically, the findings imply that companies and auditors should strengthen ESG data integration, technological readiness, and digital audit competencies to improve sustainability assurance practices.